Family and gender images in self-publishing - Klumbys, Valdemaras (Genocidas ir rezistencija, 2020)
The valuable basis of almost all the texts discussed is Catholicism. This leads to the conservative nature of the articles and the negative attitude towards the social and cultural changes that had taken place during modernization. However, the level of conservatism of self-published authors and the details of the assessment of the changes differed. Most of the authors blamed the Soviet state and the system (especially the atheism of society) for all the negative changes, while some of them believed it was a consequence of a special policy aimed at destroying the Lithuanian nation. A smaller number of authors saw the threat arising not so much from the USR as from modernization itself, and thus from the West.A lack of more diverse sources of information may have contributed to the ideological conservatism, which forced authors to rely on the interwar publications. Such a situation had intervened the perception of the changed reality and adequate response to it. This, in turn, could have reduced the impact or even prevalence of self-publishing – the diversity of opinions in the legal press was much greater.Generally, the Soviet regime was accused by selfpublished authors of promoting excessive freedom (legal abortions, simple divorce proceedings, etc.) and was criticized for destroying traditional gender roles. Therefore, the relationship of the underground authors with freedom was ambiguous – in the fight for the political freedom of the nation, personal human freedom was not valued in private life, and the texts usually emphasized a person’s duty – a person was subordinated to the idea, only not to that of the communists but also to the national idea. The fact that there were no discussions on family and gender issues in the self-published publications shows a lack of authors, the ideological unity of various publications, and a lack of liberal and democratic values in the underground movement.Some texts kind of reveal certain ideas of female emancipation; however, the longing for the traditional family and the respective gender roles dominate, and there are no hints of the need for real gender equality in a family. Instead, there is a clear link between traditional femininity and the exaltation of a woman. A hypothesis may be made that this was due to the link between gender equality with the Soviet propaganda and the reality of the USR when women were forced to endure a double workload. The image of a religious family as an antidote to pervasive immorality and degrading civil marriage can also be seen as a form of Catholic advocating, offered as an antidote to the breakdown of families and the enslavement of women. Perhaps this may have contributed to the religious revival in the early 1980s.Comparing the family and gender discourses in the publications of self-published authors and the legal press, many similarities may clearly be noticed, the most important of which is a very similar critique of the identical consequences of modernization. Sometimes disadvantages such as divorce, a small number of children in families, abortions, and the situation of women were criticized almost identically. Nevertheless, the causes of these disadvantages were searched for in a different place in self-published publications, first of all – in atheism policy. Therefore, despite the obvious hostility of self-publishing discourses to the Soviet reality and politics, they essentially only supplemented the public discourses by expressing those things that could not be made public due to the Soviet censorship (religious and anti-Soviet themes) but did not create a fundamentally different understanding of gender, family or sexuality from that prevailing in the public sphere.On the one hand, such similarity would be explained by the fact that self-published texts reflected the norms and values successfully introduced by public discourses to society. Much of the criticism of the system and reality was based namely on the postulates of the Soviet discourses, which had spread freely in public. The fact that a conservative turn in the discourses of family and gender relations took place throughout the USR in the 1970s may have contributed to this similarity.On the other hand, such a similarity can be explained by the discourses of the interwar Catholic family that had survived and preserved in society and were not influenced by Soviet propaganda. Still, it is doubtful that people could have remained unaffected by public discourses for three or four decades. However, taking into account the conservatism of the Soviet ideology and the order in the studies areas, it would be more accurate to state that no essential changes took place in Lithuania during the Soviet era in the field of family images and gender stereotypes.
Keywords: Soviet Lithuania; Soviet family; gendar equality; samizdat; modernisation